The connotations of Islamic symbols in contemporary Iraqi art: The artist (Salman Abbas) is a model - Salman Sadkhan, Alaa; Amin Mahmoud, Ayath Abdul Rahman (Al-Adab Journal, 2020)
Islamic symbols played the largest and distinctive role in showing the aesthetic image of that society that is embraced by Islamic thought. Heritage and folk symbols have crowded and harmonized into one fabric, a flexible fabric that accepts everything new society can produce and be certain of, and this does not mean that the Islamic symbols are in fact Islamic, but they are Heritage heritage extending through the ages passed down from generation to generation, generation after generation, those symbols possessed a special philosophy that did not intersect with Islamic philosophy except in a few easy ones, even though some symbols are stripped from its ancient concept as the symbol of the crescent that symbolized for God the age of God: the moon, so this symbol became a witness of a month Islamic fasting, which made him stand out and steadfast in the strength of his existence as an inevitable Islamic symbol that Muslims expect for the purpose of patience every year, and it can be said that Islamic symbols and other symbols came as a metaphorical solution and as an alternative to a speech of feelings and feelings for the symbolized so providing a rose for the lover sings thousands of fake messages and all this is mortgaged The nature of societies, the way of thinking, and what is not correct in a society that is correct at the end of our research. We were exposed to some of the Islamic and traditional symbols that appeared in the works of the artist (Salman Abbas) in an attempt It extrapolates and reveals its implications and intellectual implications inherent in it. The research included four axes: (the methodological framework) , which consists of the problem of research, the need for it, the importance of research, and the objectives of the research, then defining the search terms. As for the theoretical framework, it includes two topics: the first topic: the references of Islamic symbols in Iraqi art, the second topic: the symbolic connotations of Islamic architecture. Then the research procedures, which included the research community, the research methodology, the research sample, research tools, analysis of samples, stamping with results, conclusions, proposals, recommendations, list of sources, references, and summary in English.